Enhancing Legal Protection for Digital Transactions: Addressing Fraudulent QRIS System in Indonesia: Meningkatkan Perlindungan Hukum dalam Transaksi Digital: Mengatasi Sistem QRIS Palsu di Indonesia - Herryani, Mas Rara Tri Retno (Universitas Muhammadiyah Sidoarjo, 2023)
This study examined the legal safeguards necessary to combat fraudulent QRIS systems in digital transactions, focusing on the imperative need to protect consumers who are often more vulnerable than business entities in the digital transaction process. Employing a normative legal research methodology, the study utilized a legislative approach and concept analysis to deliver its findings. The study revealed that preventive legal protection, manifesting as increased public awareness and understanding of the QRIS system, its use, and associated criminal potentials, is essential. Repressive legal protection should be implemented by enhancing the capacity and infrastructure of law enforcement agencies. In cases of internal issues with the QRIS system, the liability of the system's creator or issuer must be clearly defined. The electronic system's execution can be managed by the electronic system provider or delegated to e-business agent operators, underlined by good faith, transparency, accountability, fairness, and prudence. This research underscores the importance of extensive public socialization and training on the use and risks of the QRIS system, providing implications for bolstering consumer protection laws, enhancing law enforcement capacity and infrastructure, and refining electronic transaction regulations in Indonesia. Highlights: The vulnerability of consumers in digital transactions necessitates robust legal safeguards, particularly regarding the use of the QRIS system. Both preventive (educational) and repressive (enforcement) legal protections are vital to combat fraudulent digital transactions and enhance consumer confidence. Enhancing law enforcement capabilities and infrastructure, as well as clearly defining the liability of QRIS system issuers, is imperative for maintaining the integrity of digital transactions. Keywords: Legal protection, digital transactions, fraudulent QRIS, consumer protection, law enforcement capacity.